Effect of oral dosing of live and autoclaved culture of Ruminococcus flavefaciens FD-1 on rumen bacterial and fungal populations in Murrah buffaloes - Kumar, Brishketu; Kumar, Dinesh; Mahesh, MS; Sheel, Rakesh (Indian Journal of Dairy Science, 2021)
Dietary interventions aiming at increasing the number and activities of beneficial gut microbes could enhance digestive functions as well as the long-term welfare of dairy animals. In the present experiment, the effect of supplementation of a novel bacterial culture Ruminococcus flavefaciens FD-1 isolated from the rumen liquor of Murrah buffaloes was studied for its effect on rumen microbial populations enumerated using the most probable number technique. Three permanently fistulated buffaloes maintained on a high fibre diet were used as the source of rumen fluid for bacterial isolation that was subsequently testedin vivo. Twelve healthy mid-to-late lactating buffaloes in their second to third parity were divided into two similar groups of six each with a mean body weight of 601.5 kg. One group (LBC) was dosed with 300 mL of live bacterial culture, whereas an equal volume of autoclaved bacterial culture was dosed in anothergroup (ABC) for a period of one month. The treatment-wise effect of supplementation of R. flavefaciens FD-1 culture was evident in an increase (P